Analyzing Individual Psychology of Main Figures in the Pursuit of Happiness Film - Mutmainatul Mardiyah; Nur Fatih Rahmawati (Candradimuka: Journal of Education, 2023)
The purpose of this study was to identify and analyze the individual psychology of the main character in the film The Pursuit of Happiness. The research method used is descriptive qualitative. Based on an analysis of 30 data, 6 individual psychology of the main character were found. The types of individual psychology and percentages are as follows: inferiority complex (3 data) or 10%, superior (9 data) or 30%, lifestyle (10 data) or 33.3%, creative self (1 data) or 3.3%, pseudo-goals (3 data) or 10%, and social interest (4 data) or 13.3%.